WEBSITE APPLICATION CREATION FOR E-JOURNAL - Anggi Annur Septia; Rima Tamara Aldisa (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research aims to develop a website application which aims to facilitate the management and distribution of electronic journals (e-journals) efficiently. The development methods used are user needs analysis, system design, implementation and evaluation. This application is designed to provide an easy-to-use platform for journal managers to upload, manage and publish articles online. Apart from that, this application is also equipped with a search feature that makes it easier for readers to find articles that are relevant to the topic of interest. Evaluation is carried out through functionality testing and user satisfaction to ensure the performance and usability of this application. The research results show that this application can increase efficiency in managing and distributing electronic journals and provide a satisfactory user experience.